Hours of work and retirement behaviour - C. Sofia Machado; Miguel Portela (IZA Journal of European Labor Studies, 2014)
Using a novel dataset from the 2006 Portuguese Labour Force Survey this paper examines the impact of a voluntary reduction in hours of work, before retirement, on the moment of exit from the labour force. If, as often suggested, flexibility in hours of work is a useful measure to postpone retirement, then a reduction in working hours should be associated with retirement at later ages. Results prove otherwise suggesting that reducing hours of work before retirement is associated with early exits from the labour force. A reduction in hours of work seems to signal the worker's wish to retire sooner rather than to announce the desire of remaining in the labour market. This result may enclose the need for some alternative policy strategies regarding working hours.
Keywords: J14; J26; J22; J21; 330